2005
DOI: 10.1099/jmm.0.45824-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of vancomycin-resistant enterococci in humans and animals in the Czech Republic between 2002 and 2004

Abstract: , a total of 6023 rectal swabs from humans in the Czech Republic were evaluated and 821 Enterococcus spp. strains were isolated. Nine strains (1 . 1 %) were identified as vancomycin-resistant enterococci (VRE). Two strains were VanA Enterococcus faecium, one strain was VanB Enterococcus faecalis and six strains were VanC Enterococcus casseliflavus. In total, 527 Enterococcus spp. strains were isolated from poultry breeds of which 11 (2 . 1 %) were VRE. Most (54 . 5 %) were identified as VanA E. faecium. Cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The results of the current study were similar to the study of [10], who identified 9 isolates (1.1%) as vancomycin-resistant Enterococci (VRE), two of them had the VanA gene, one wasolate had the VanB gene, and six wasolates had The VanC gene. [11] conducted a study of the genetic content of isolates of Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the current study were similar to the study of [10], who identified 9 isolates (1.1%) as vancomycin-resistant Enterococci (VRE), two of them had the VanA gene, one wasolate had the VanB gene, and six wasolates had The VanC gene. [11] conducted a study of the genetic content of isolates of Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 87%
“…), Czech Republic (Kolar et al . ) and Saudi Arabia (Qadri and Postle ). The highest documented VRE colonization rates occur in Palestine (Hijazi et al .…”
Section: Discussionmentioning
confidence: 99%
“…faecium carrying the vanA gene followed by Ent. faecalis with vanB (Kolar et al 2002(Kolar et al , 2005(Kolar et al , 2006. Information on VRE in wildlife is limited.…”
Section: Discussionmentioning
confidence: 99%